Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content:1. Difficulties Faced by Married Female Employees at the University of ZakhoDr. Sajida Ismail Abdullah2. Pollination operations and field organization in the territory of the Taza Province – MoroccoDr. ABDELOUAHED BOUBERRIA, Dr. Abdelhafid Hammimi, Dr. Mohammed Abahrour, Dr. Mohammed Errafik3. Lynch Company's River Navigation Franchises in Mesopotamia: Economic Control and Local Responses 1860-1908Ali Mohammed Qader
Keywords: Journal of Human and Social Sciences